2022
DOI: 10.1038/s41598-022-22423-6
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of hepatic encephalopathy: bile duct ligation induces brain ammonia overload, glial cell activation and neuroinflammation

Abstract: Hepatic encephalopathy (HE) is a common complication of chronic liver disease, characterized by an altered mental state and hyperammonemia. Insight into the brain pathophysiology of HE is limited due to a paucity of well-characterized HE models beyond the rat bile duct ligation (BDL) model. Here, we assess the presence of HE characteristics in the mouse BDL model. We show that BDL in C57Bl/6j mice induces motor dysfunction, progressive liver fibrosis, liver function failure and hyperammonemia, all hallmarks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 74 publications
5
20
0
Order By: Relevance
“…Confirming earlier data [ 24 ], no significant differences were detected in the percentage of microglia and astrocytes in BDL mice at either timepoint compared to sham controls, indicating there is no apparent glial cell death nor proliferation (Fig. 1 B, C).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Confirming earlier data [ 24 ], no significant differences were detected in the percentage of microglia and astrocytes in BDL mice at either timepoint compared to sham controls, indicating there is no apparent glial cell death nor proliferation (Fig. 1 B, C).…”
Section: Resultssupporting
confidence: 92%
“…1 A). These timepoints were chosen as microglial morphological changes are apparent in BDL mouse brains 14 days after induction, while astrocyte reactivity becomes morphologically apparent 28 days after induction [ 24 ]. After exclusion of debris, doublets and dead cells, microglia were defined as CD45 lo-int CD11b + cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact pathophysiological mechanisms of HE are not fully understood. However, numerous studies have demonstrated that HE has complex pathology at the cellular molecular levels, e.g., astrocyte dysfunction plays a critical role in the pathogenesis of both forms of HE (i.e., ALF and CLD) [ 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, substances including ammonia, glutamine, glutamate, aromatic amino acids, lactate, alanine, bile acids, and neurosteroids accumulate in the brain parenchyma during HE [ 10 , 11 , 12 ] and are directly implicated in the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%